Parents Need More Support: A Qualitative Study of the Experiences of Australian Parents Who Are Waiting for Surgical Intervention for Their Children With Otitis Media. (October 2020) - Stephens, Jacqueline H; O'Keefe, Maree; Schembri, Mark; Baghurst, Peter A
Objective: To explore the experiences, expectations, and motivations of parents/caregivers of children with otitis media who were booked to undergo tympanostomy tube insertion. Method: A cross-sectional cohort study was conducted using semistructured interviews with 39 parents. Interviews were conducted via telephone and analyzed for key themes. Results: Three themes emerged that incorporated a range of subthemes: (1) the impact of the child's underlying condition on the family, (2) the cues and prompts that influenced parents to seek intervention, and (3) the parents' expectations of the health-care system. The child's otitis media disrupted the day-to-day functioning of the family and the child's well-being, but despite this, the families found ways to adapt and cope. Parents were influenced by their friends, family, and medical practitioners when making treatment decisions and had differing expectations of the health-care system. Conclusion: Parents need support during their child's illness to help with pressures placed on the family and also in making health-care decisions for their child. Clinicians should consider these issues when discussing treatment options with parents.